Perceptions of English Specialized Student Teachers Towards Teaching Practice - Kandel, Rajan Kumar; Bist, Resham Bahadur (English Language Teaching Perspectives, 2024)
In the present landscape of evolving teacher education programme, it is essential to know the perceptions of English Specialized Student Teachers (ESSTs) about Teaching Practice (TP) in general and university supervision and the role of cooperative schools in particular in making their TP experiences effective. This paper aims to analyze the perceptions of ESSTs to find out the effectiveness of university supervision and the role of cooperating schools in TP. For the study, a quantitative case study was applied as a research methodology. Data were obtained through questionnaires from the ESSTs of three campuses located in Surkhet Nepal. The findings revealed that TP played a pivotal role in developing qualified, trained, and confident teachers. Despite the satisfactory role of university supervision in TP, ESSTs felt stressed and worried due to the heavy workload related to the TP. Moreover, they perceived the important role of cooperative schools where they learnt from their strengths and areas that required improvement during TP. Therefore, university supervision and school administration should make TP flexible and engaging for ESSTs by motivating them to avoid their presupposition that TP is just a time-consuming, rigid, and boring task. In this regard, the study suggests enhancing the current collaboration between schools and universities for the effectiveness of teacher preparation addressing the issues. Moreover, it offers insights to enhance teacher preparation programme and improve the overall quality of education.